PROGRAM BIMBINGAN DAN KONSELING MAHASISWA FKIP UNTIRTA BERBANTUAN SOFTWARE ANALISIS TUGAS PERKEMBANGAN - Deasy Yunika Khairun; Meila Dwi Nurmala (Jurnal Penelitian Bimbingan dan Konseling, 2020)
The aim of research is for desaigning guidance and counseling program based on description of 5th grade student’s development step in all of study program in FKIP Untirta by using Inventori Tugas Perkembangan (ITP) and Analisis Tugas Perkembangan (ATP) software. This research was held in FKIP University of Sultan Ageng Tirtayasa. Subject of this research is 5th grade of students of all study program in FKIP University of Sultan Ageng Tirtayasa 2019/2020 academic year. Research using descriptive quantitave methods and using Inventory Tugas Perkembangan (ITP) instrument.